2021
DOI: 10.3390/ijms23010308
|View full text |Cite|
|
Sign up to set email alerts
|

Pathomechanisms of Vascular Depression in Older Adults

Abstract: Depression in older individuals is a common complex mood disorder with high comorbidity of both psychiatric and physical diseases, associated with high disability, cognitive decline, and increased mortality The factors predicting the risk of late-life depression (LLD) are incompletely understood. The reciprocal relationship of depressive disorder and age- and disease-related processes has generated pathogenic hypotheses and provided various treatment options. The heterogeneity of depression complicates researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 232 publications
(273 reference statements)
1
27
0
4
Order By: Relevance
“…A focus on prevention is, therefore, key to reduce the burden of late-life depression. Vascular risk factors are increasingly recognized as potential contributors to the development of late-life depression and, thus, as potential targets for early preventive therapies …”
Section: Introductionmentioning
confidence: 99%
“…A focus on prevention is, therefore, key to reduce the burden of late-life depression. Vascular risk factors are increasingly recognized as potential contributors to the development of late-life depression and, thus, as potential targets for early preventive therapies …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, depression that begins around or after the age of 60 year (i.e., late-onset depression) is hypothesized to be a contributor to, or result of, accelerated brain and cognitive aging and both major and minor depression in older adults increases the risk of cognitive decline and conversion to dementia [ 34 ]. This may be due to both depression and aging having combined adverse effects on similar neural networks [ [35] , [36] , [37] ], neurotransmitter functions [ 38 ], and other biological processes (e.g., vascular changes, neuroinflammation) [ [39] , [40] ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas vascular risk factors failed to verify the vascular depression hypothesis in PD (Ou et al 2018 ), others suggested that co-morbid cerebral small-vessel disease (CSVD), marked by WM hypointensity, number of lacunes and microbleeds, may affect multiple functional domains in PD, including motor, cognitive and emotional impairments (Chen et al 2021 ). Many studies have provided evidence that large WM hypointensity volumes, subcortical lacunes and other markers for CSVD are associated with increased risk for depressive symptoms (Geraets et al 2021 ; Jellinger 2021 , 2022b ; Nunes et al 2022 ; Wang et al 2020 ), since they are disturbing cortico-subcortical neuronal circuits causing microstructural dysfunctions of major brain connections involved in emotion and other important behaviors, thus suggesting an association between CSVD and depression (Empana et al 2021 ; Kim and Han 2021 ; Nunes et al 2022 ).…”
Section: Other Pathogenic Factors In Dpdmentioning
confidence: 99%